Optimization and Preparation of Tallow with a Strong Aroma by Mild Oxidation - Yanjing Jin; Junaid Raza; Huanlu Song; Lijin Wang; Qiaojun Wang; Guoli Ma; Yang Xiao (Molecules, 2022)
This study was performed to extract and separate the volatiles with solid-phase microextraction (SPME), and was conducted to analyze volatile odor compounds qualitatively and quantitatively in the production of a strong aroma tallow by mild oxidation. A total of 51 odor compounds were detected in the tallow smelted under different conditions. It was found that the high proportion of aldehydes was an important feature of the aroma components in the oxidized melted tallow, such as 1-hexanal, heptanal, nonanal, octanal, benzaldehyde, etc. Through the determination of various indicators, sensory evaluation, and the gas chromatography-olfaction–mass spectrometry (GC-O–MS) analysis and, in combination with response surface methodology, the optimal process parameters for oxidative smelting of tallow were determined as follows: a reaction temperature of 149.61 °C, a reaction time of 31.68 min, and an airflow rate of 97.44 L/h. The accelerated oxidation test further verified the quality of the oxidized tallow.